The Influence of Motivation, Financial Literacy, and Minimum Capital on Accounting Students’ Investment Interest at Tanjungpura University - Amelia, Cindy; Puspitasari, Ayu; Rusmita, Sari (International Journal of Economics Studies, 2025)
This research focuses on identifying the impact of investment motivation, financial literacy, and minimum investment capital on students' interest in investing in the capital market. This research utilizes primary data collected through questionnaires. The research subjects were active accounting students at Tanjungpura University. The research population used purposive sampling techniques, finally getting 90 students who had taken courses on investment and capital markets. The research utilizes a quantitative approach, by processing data using SPSS version 25. The findings from the research show that investment motivation has a positive influence on students' interest in investing in the capital market, while financial literacy and minimum investment capital have no significant influence.